COMPREHENSIVE REVIEW OF EXTRICATION TECHNIQUES IN VEHICLE RESCUE OPERATIONS. - Abdullah Rasheed Aljahim, Hassan Mohammed Kadam Almuhanna, Rakan Saleh Dhafer Alharith, Bilal Ali Alshehri, Jabril Mohammed Hakami, Mohammed Wafi Saad Almadhi, Faisal Saud Abdulhaq, Abdulrahman Ahmed Alzahrani, (Chelonian Research Foundation, 2023)
In this article, the involvement of pharmacists in smoking cessation interventions in managing patient health outcomes and the smoking-related disease burden will be reviewed. A thorough literature review is carried out to look at these interventions' effectiveness. Consequently, suggestions are provided that can be used in healthcare practice and policy. The paper offers an introductory section about the significance of smoking termination and pharmacists' role in health care systems. A comprehensive literature review examines both the holistic and therapeutic frameworks, interacting approaches, and scientific evidence supporting pharmacist-led interventions. Ways of approving the research are discussed first, and then the research results are unraveled using statistics and maybe illustrations of graphs, figures, and tables to stress out the key points. The talk itself may reveal the findings, formulate their strengths and weaknesses, and explore the potential obstacles and opportunities. Finally, the concluding section highlights the implications of our work so far and suggests strategies to make pharmacist-led smoking cessation efforts more effective. Keywords: Pharmacist, smoking cessation, interventions, effectiveness, patient outcomes